Synthesis and Characterization of Cellulose-based Eco-Friendly Hydrogels (Rajshahi University Journal of Science and Engineering, 2016)
Biodegradable nature of hydrogels is highly appreciable and core expectation at present time. Cellulose and cellulose derivatives can be copolymerized in producing green hydrogels for improving the absorption performance of many adsorbent products. Hydrogels are polymeric substances and due to hydrophilic functional groups in their structure capable of holding large amount of water compared to its body mass. Crosslinking is one of the simplest reactions used to improve the physico-chemical properties of cellulose and cellulose derivatives. In the present paper an innovative cellulose based environment friendly hydrogel was experimentally synthesized as an alternative to acrylate-based synthetic hydrogels for personal care product and other absorption purposes. The cellulose based hydrogels were prepared by free radical graft copolymerization reaction of cotton with acrylic acid (AA) and acrylamide (AM) using N,N-methylne-bis-acrylamide (MBA) as a crosslinker in the presence of initiator potassium persulphate (K2S2O8) system. The maximum water absorption capacity of the prepared hydrogels were 50 g/g in deionized water. Optimized preparation condition was invstigated depending on monomer concentration, initiator concentration, crosslinker concentration,pH, time and temperaturefor equilibrium water absorption which were 120%, 10%, 5%, 7, 2h and 50°C respectively.For structural characterization FTIR spectroscopy, SEM analysis, TGA and XRD technique were performed. The result ensuresthat the characteristic of prepared hydrogel can be effectively used in personal absorbent products, tissue engineering, biomedical application etc. and as adsorbent material in polluted water treatment.